WHY ISLAMISM FAILED IN SYRIA - Kostanian, Ararat (Journal of Terrorism Studies, 2023)
The Arab Spring has not fulfilled the desires of millions of demonstrators in Middle East. The desires to see the expanded role of the civil society has been muted by the Islamists and particularly by the Muslim Brotherhood. The Article puts the focus on the failure of Islamism in Syria during the uprising for several reasons, such as the inability of the Muslim Brotherhood to shape a new leadership, and its rejectionist agenda that had nurtured skepticism by the opposition factions. Furthermore, the Syrian Muslim Brotherhood had been unable to change its political motivation and kept insisted on shifting the Syrian political system. Moreover, the failure of the Muslim Brotherhood in Syria was its dependency on regional powers and its cooperation of the with the extremist groups has put them on the side of the terrorist groups and neutralized the argument that the West and precisely the US has been circulating for years as Muslim Brotherhood could be considered a moderate Islamist organization. This article reveals the identical ideology and strategy of the Syrian Muslim Brotherhood and the extremist groups in Syria which hasn’t been studied before in past-present context.